Post-qualitative inquiry in the first person : A conversation with Elizabeth Adams St. Pierre (Praxis Educativa, 2026)
Elizabeth Adams St. Pierre is family. Academic family. Originally mentored by figures like Laurel Richardson and Patty Lather, she became acquainted with poststructuralism through feminism in the nineties and paid enough heed to the cognitive dissonance she experienced in her dissertation process to start challenging qualitative methodology at that time. In this century, after maturing this uneasiness, she created, and coined, Post-Qualitative Inquiry which, as she often says, is not a methodology but rather a becoming which operates on a different ontoepistemological basis. She has ever since worked on experimenting research that demands a lot of hard work in reading and writing, but also a great deal of imagination and courage, to avoid ‘the trap of methodology’. Her work has been unparalleled and so is her kindness and candor. In this conversation we delved into her beginnings, what matters the most to her, and her investment in doing academic work that really counts.
Keywords: Post-Qualitative Inquiry; Poststructuralism; Ontoepistemological; Antimethodology